Active slurry, positive pole piece as well as preparation method and application of positive pole piece
By optimizing the formulation of the active slurry, the electrochemical performance and structural stability of the positive electrode sheet of the hybrid capacitor are improved, and the problem of difficulty in meeting high energy density and high power density at the same time is solved, thus achieving high performance and long life In combination, it provides technical support for efficient energy storage applications.
Patent Information
- Application Number
- CN202411654894.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Existing hybrid capacitor positive electrode materials are difficult to meet the needs of high energy density and high power density at the same time, and commercial positive electrode materials are mainly concentrated in ternary materials and lithium iron phosphate technology routes, which cannot meet the market's demand for high-performance and low-cost hybrid capacitors. .
An active slurry is provided, including an active material and an organic solvent, with a solid content of 45% to 60% by weight, wherein the raw material of the active material includes 93.5% to 97.5% by weight, and 1.5% by weight of the binder based on mass fraction. ~4.0 wt% and 1.0 wt% to 2.5 wt% of the conductive substance, optimize the proportion and solid content of the active substance, binder and conductive substance, and improve the overall electrochemical performance and structural stability of the positive electrode sheet.
By optimizing the formulation of the active slurry, the energy density, power density and cycle stability of the positive electrode sheet are improved, and the combination of high performance and long life is achieved, providing reliable technical support for efficient energy storage applications.
Smart Images

Figure CN119480216A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage, and in particular relates to an active slurry, a positive electrode sheet, and a preparation method and application thereof. Background Art
[0002] Hybrid capacitors achieve high energy density and high power density energy storage through the electric double layer capacitance effect and Faraday reaction, and have broad application prospects. Its working principle includes two main processes: on the one hand, ions undergo reversible adsorption and desorption processes on the surface of electrochemically active materials; on the other hand, lithium ions participate in reversible Faraday chemical reactions in the bulk of the electrode material. Common hybrid capacitor electrode materials are usually carbon materials or conductive polymers with high specific surface area, which store charge through the electric double layer effect; at the same time, the addition of active materials such as metal oxides or conductive polymers enables the electrodes to further store electrical energy through chemical reactions, thereby improving the overall performance of the capacitor.
[0003] The design of the positive electrode material for hybrid capacitors is particularly critical. It requires both capacitor active materials with high specific surface area (such as activated carbon) and battery active materials that can undergo redox reactions with lithium ions (such as lithium nickel cobalt manganese oxide, lithium iron phosphate, etc.). During the charging and discharging process, the capacitor active material affects the energy characteristics of the capacitor through the adsorption and desorption process of charges, while the diffusion rate of lithium ions in the battery material determines its power characteristics. Therefore, optimizing the production process of the positive electrode sheet will help improve the energy density and power density of the hybrid capacitor and meet the development needs of the "double high" hybrid capacitor.
[0004] In the field of hybrid capacitor research, foreign technology development is relatively advanced. Companies such as Japan's JM Energy and South Korea's VINATech have accumulated rich experience in the research and development of hybrid capacitor monomers, and are at the international leading level in material science, electrochemistry and engineering technology. The wide application of hybrid capacitors in transportation, industrial control, consumer electronics and other fields has further promoted the innovation and upgrading of positive electrode materials, and helped the research and development of high-performance hybrid capacitors.
[0005] In China, the technical research and industrialization of hybrid capacitors have made significant progress. Shanghai Aowei, Ningbo CRRC and other companies have achieved large-scale production of hybrid capacitors, and their products are widely used in electric buses, solar energy storage and other fields. In addition, many domestic universities and research institutions are also actively promoting the innovation of positive electrode materials for hybrid capacitors. Zhejiang Normal University and Nanyang Technological University jointly developed a porous CoO / Co-Cu-S multi-level tubular heterostructure material with a special pore structure, which showed excellent electrochemical performance and excellent rate performance and cycle stability, which provided a useful research idea for the development of high-performance electrode materials. In addition, the team of Dalian Institute of Chemical Physics of the Chinese Academy of Sciences used the "double matching" strategy to develop a rocking chair hybrid energy storage device with the characteristics of lithium-ion batteries. It used orthorhombic phase Nb2O5 and high-nickel ternary material NCA as positive and negative electrodes to construct a hybrid capacitor in which lithium ions shuttle back and forth between electrodes, successfully achieving both high energy density and high power density. At a power density of 9.1kW / kg, an energy density of 83Wh / kg is achieved, providing new ideas for the design of "double-high" hybrid energy storage devices.
[0006] At present, the selection of positive electrode materials and the preparation process of the electrode are the key to improving the performance of hybrid capacitors. At present, commercial positive electrode materials are mainly concentrated on ternary materials and lithium iron phosphate technology routes, but a single material cannot meet the needs of high energy and high power density. Therefore, it is urgent to develop a positive electrode preparation method that combines battery and capacitor characteristics to meet the market demand for high-performance, low-cost hybrid capacitors. Summary of the invention
[0007] The purpose of the present invention is to solve the above-mentioned deficiencies and provide an active slurry, a positive electrode sheet and a preparation method and application thereof.
[0008] In the first aspect, an active slurry adopts the following technical solution:
[0009] An active slurry, comprising an active material and an organic solvent, wherein the solid content of the active slurry is 45wt% to 60wt%;
[0010] The raw materials of the active material include, by mass fraction:
[0011] Active matter, 93.5 wt% to 97.5 wt%;
[0012] Binder, 1.5wt% to 4.0wt%;
[0013] Conductive material, 1.0wt% to 2.5wt%.
[0014] Furthermore, the active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and activated carbon;
[0015] The binder includes one or more of polyvinylidene fluoride, polyvinyl alcohol and polytetrafluoroethylene;
[0016] The conductive material includes one or more of carbon black, graphene, carbon tubes, and conductive graphite;
[0017] The organic solvent is one or more of N-methylpyrrolidone, dimethylformamide and dimethyl sulfoxide.
[0018] Furthermore, the active material includes lithium nickel cobalt manganese oxide and activated carbon, and the mass ratio of the lithium nickel cobalt manganese oxide to the activated carbon is 1:10 to 10:1.
[0019] Furthermore, the conductive material includes graphene and carbon black, and the mass ratio of the graphene to the carbon black is 0.2:1.0 to 1.0:1.0;
[0020] Alternatively, the conductive material includes carbon tubes and carbon black, and the mass ratio of the carbon tubes to the carbon black is 0.2:1.0 to 1.0:1.0.
[0021] In the second aspect, a method for preparing an active slurry adopts the following technical solution:
[0022] A method for preparing an active slurry comprises the following steps:
[0023] Under vacuum, the binder is added to the organic solvent for the first stirring, the conductive material is then added for the second stirring, and the active material is finally added for the third stirring. After preliminary mixing, high-speed stirring and low-speed stirring are performed in sequence to obtain the active slurry.
[0024] Furthermore, under the vacuum state, the vacuum degree is 10 -2 Pa~10 -3 Pa.
[0025] Further, the first stirring includes the following process: stirring at a rotation speed of 80 rpm to 120 rpm for 4 min to 6 min, then stirring at a rotation speed of 250 rpm to 350 rpm for 4 min to 6 min, and finally stirring at a rotation speed of 500 rpm to 700 rpm for 250 min to 350 min;
[0026] The second stirring comprises the following process: stirring at a rotation speed of 80 rpm to 120 rpm for 4 min to 6 min, then stirring at a rotation speed of 250 rpm to 350 rpm for 4 min to 6 min, and finally stirring at a rotation speed of 500 rpm to 700 rpm for 150 min to 200 min;
[0027] The third stirring includes the following process: stirring at a rotation speed of 80 rpm to 120 rpm for 4 min to 6 min, then stirring at a rotation speed of 250 rpm to 350 rpm for 4 min to 6 min, and finally stirring at a rotation speed of 500 rpm to 700 rpm for 800 min to 900 min;
[0028] The high-speed stirring process: stirring at a rotation speed of 1200 rpm to 1300 rpm for 150 min to 200 min;
[0029] The low-speed stirring process is as follows: stirring at a rotation speed of 15 rpm to 25 rpm for 45 min to 65 min.
[0030] In a third aspect, a positive electrode sheet adopts the following technical solution:
[0031] A positive electrode sheet, comprising a current collector and an active coating layer formed by curing the active slurry as described above on the surface, wherein the surface density of the active coating layer is 25 mg / cm 2 ~50mg / cm 2 , the thickness of the active coating layer on one side is 100 μm to 160 μm;
[0032] Both sides of the current collector are coated with a graphene coating of 1 μm to 3 μm; the current collector comprises one of a smooth or frosted perforated aluminum foil or a non-porous aluminum foil.
[0033] In a fourth aspect, a method for preparing a positive electrode sheet adopts the following technical solution:
[0034] A method for preparing a positive electrode sheet comprises the following steps: coating the active slurry on the surface of a current collector, with a coating roller speed of 300 mm / min to 350 mm / min and a roller speed ratio of 1.3 to 1.7, drying at a temperature of 120°C to 150°C, and then rolling to control the compaction degree to 2.0 to 2.4 g / cm 3 , and the positive electrode sheet is obtained.
[0035] In a fifth aspect, an application of a positive electrode sheet adopts the following technical solution:
[0036] An application of the positive electrode plate as described above in electric vehicles, grid energy storage, industrial automation and renewable energy systems.
[0037] Beneficial effects of the present invention:
[0038] The present invention provides an active slurry, which serves as a coating material for a positive electrode plate. By optimizing the ratio and solid content of active substances, binders and conductive substances, the overall electrochemical performance and structural stability of the positive electrode plate are improved; a high ratio of active substances enhances the capacity performance of the coating, which helps to improve the energy density of the hybrid capacitor; an appropriate amount of binder ensures that the coating layer has good adhesion and mechanical strength, reduces the risk of coating peeling during the cycle, and extends the service life of the plate; at the same time, a reasonable ratio of conductive substances improves the electron conduction efficiency, reduces the internal resistance, and enhances the power characteristics of the plate; this active slurry formula not only enables the positive electrode coating to have excellent charge storage and transmission capabilities, but also maintains the stability of the plate after multiple cycles, achieves a combination of high performance and long life, and provides reliable technical support for efficient energy storage applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The charge and discharge curve of the 2032 button cell composed of the positive electrode sheet of Example 1 at a current density of 0.5C;
[0040] Figure 2 This is a test diagram of the charge and discharge of a 2032-type button battery composed of the positive electrode sheet of Example 1 at different rates;
[0041] Figure 3 This is a test diagram of the cycle performance of the 2032 button cell composed of the positive electrode sheet of Example 1 at a rate of 0.5C. DETAILED DESCRIPTION
[0042] The following is a further specific description of an active slurry, a positive electrode plate and a preparation method thereof described in the present invention in conjunction with the examples. For the sake of simplicity of description, this document cannot list all alternative technical features and implementation schemes contained in the present invention. Therefore, those skilled in the art should know that any technical features and implementation schemes in this embodiment do not limit the scope of protection of the present invention, which includes any alternative technical features and implementation schemes adopted by all those skilled in the art without creative labor. Specifically, the implementation schemes obtained by replacing any technical feature in the present invention or combining any two or more technical features provided by the present invention should be within the scope of protection of the present invention.
[0043] This embodiment provides an active slurry, the active slurry includes an active material and an organic solvent, and the solid content of the active slurry is 45wt% to 60wt%;
[0044] The raw materials of active materials are calculated by mass fraction, including:
[0045] Active matter, 93.5wt% to 97.5wt%;
[0046] Binder, 1.5wt% to 4.0wt%;
[0047] Conductive material, 1.0wt% to 2.5wt%.
[0048] The active slurry provided in this embodiment achieves excellent electrochemical performance and structural stability through a specific ratio of active materials and organic solvents. The solid content is set at 45wt% to 60wt%, ensuring the appropriate viscosity and uniform dispersion of the slurry, making the coating process more stable and efficient; the high proportion of active substances in the active material gives the slurry a higher energy storage capacity and energy density; the appropriate amount of binder enhances the adhesion and mechanical strength of the coating, prevents the coating from falling off during the cycle, and improves the durability of the electrode. At the same time, the addition of conductive substances forms a good conductive network, effectively reducing the internal resistance and improving the current conduction performance.
[0049] This formula combination optimizes the overall performance of the active slurry, ensures the stability and efficient conductivity of the positive electrode during multiple charge and discharge cycles, and meets the application requirements of high energy density and long life; the slurry provides a solid material foundation for achieving higher performance energy storage devices.
[0050] In some embodiments, the active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and activated carbon;
[0051] The binder includes one or more of polyvinylidene fluoride, polyvinyl alcohol and polytetrafluoroethylene;
[0052] The conductive material includes one or more of carbon black, graphene, carbon tube, and conductive graphite;
[0053] The organic solvent is one or more of N-methylpyrrolidone, dimethylformamide and dimethyl sulfoxide.
[0054] The diverse selection of active materials, binders, conductive materials and organic solvents ensures the high energy density, excellent conductivity and long cycle life of the positive electrode. By selecting lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, activated carbon, etc., the electrode can achieve higher capacity and voltage output to meet different energy storage needs. The application of a variety of binders (such as polyvinylidene fluoride, polyvinyl alcohol, etc.) enhances the adhesion and flexibility of the coating and the substrate, avoids possible peeling during charging and discharging, and improves the stability of the electrode.
[0055] In terms of conductive materials, by adding materials such as carbon black, graphene, and carbon tubes, an efficient conductive network is constructed, which significantly improves the efficiency of electronic conduction, reduces resistance, and increases power density. In particular, the high conductivity of graphene and carbon tubes enables the pole piece to maintain excellent conductivity at high rates. N-methylpyrrolidone (NMP), dimethylformamide, and dimethyl sulfoxide are organic solvents with good solubility, making the slurry mixing more uniform, and providing appropriate viscosity and fluidity to ensure the formation of a uniform coating during coating.
[0056] The flexibility of this material combination provides a wide range of options for the application expansion of the positive electrode plate, making it not only superior in energy density and power density, but also with extremely high structural stability, meeting the needs of different energy storage devices for long cycle life and high energy output.
[0057] In some embodiments, the active material includes lithium nickel cobalt manganese oxide and activated carbon, and the mass ratio of lithium nickel cobalt manganese oxide to activated carbon is 1:10 to 10:1.
[0058] Using lithium nickel cobalt manganese oxide and activated carbon as the active material combination, and setting their mass ratio in the range of 1:10 to 10:1, can achieve an ideal balance between energy density and power density. As a high-capacity battery active material, lithium nickel cobalt manganese oxide (NCM) has a high energy density and can provide significant energy storage capacity for the positive electrode; while activated carbon has a high specific surface area, which is conducive to the rapid charge adsorption and desorption process, thereby improving power density and charging and discharging speed.
[0059] By adjusting the ratio of lithium nickel cobalt manganese oxide and activated carbon, performance optimization can be achieved according to different application requirements. A higher ratio of lithium nickel cobalt manganese oxide is suitable for application scenarios that require higher energy density, such as energy storage systems; while a higher ratio of activated carbon can enhance the power performance and cycle stability of the electrode, which is suitable for equipment that requires high power output. The flexibility of this combination not only expands the application field of the positive electrode, but also ensures the best electrochemical performance under various conditions, improving the overall energy storage efficiency and durability of the hybrid capacitor.
[0060] In some embodiments, the conductive material includes graphene and carbon black, and the mass ratio of graphene to carbon black is 0.2:1.0 to 1.0:1.0;
[0061] Alternatively, the conductive material includes carbon tubes and carbon black, and the mass ratio of the carbon tubes to the carbon black is 0.2:1.0 to 1.0:1.0.
[0062] Graphene and carbon tubes can effectively improve the continuity of electron conduction paths and the stability of electrode materials due to their high conductivity and strong mechanical strength; carbon black, as a traditional conductive filler, has stable electrochemical properties. After forming a composite with graphene or carbon tubes, it can supplement the defects in the conductive network and enhance the overall conductivity.
[0063] By adjusting the ratio of graphene or carbon tubes to carbon black, a balance can be achieved between high conductivity and cost control; a higher proportion of graphene or carbon tubes helps to form an excellent conductive network, which is suitable for applications requiring high power output; while a higher proportion of carbon black improves the stability and dispersibility of the slurry, which is suitable for scenarios with longer cycle life; this conductive material not only reduces the internal resistance of the slurry, but also ensures the integrity of the structure during multiple charge and discharge cycles, thereby enhancing the power characteristics, energy density and long-cycle stability of the positive electrode.
[0064] This embodiment provides a method for preparing an active slurry, comprising the following steps:
[0065] Under vacuum, the binder is added to the organic solvent for the first stirring, the conductive material is then added for the second stirring, and the active material is finally added for the third stirring. After preliminary mixing, high-speed stirring and low-speed stirring are performed in turn to obtain an active slurry.
[0066] By adding binder, conductive material and active material in sequence under vacuum and stirring them in steps, the uniformity, stability and electrochemical performance of the slurry can be significantly improved; first, adding binder and stirring for the first time in a vacuum environment effectively prevents bubble entrapment and ensures that the binder is fully dissolved and evenly dispersed; then, adding conductive material and stirring for the second time gradually forms a conductive network, which improves the conductivity of the slurry; finally, by adding active material and stirring for the third time, the active material is fully mixed with the conductive network and binder, ensuring the electrochemical activity and uniform distribution of the material.
[0067] The subsequent high-speed stirring further improves the dispersion and fluidity of the slurry, allowing the various components to be tightly combined; the low-speed stirring reduces bubbles and unstable factors, improving the stability of the slurry and the coating effect. The staged stirring of the entire process ensures the rheological properties of the slurry, greatly improving the density, durability and cycle life of the positive electrode sheet formed after coating, thereby achieving high energy density and high power output.
[0068] In some embodiments, the vacuum degree is 10 -2 Pa~10 -3 Pa.
[0069] Set the vacuum level at range, which can significantly improve the uniformity and overall quality of the slurry; in this vacuum state, the air in the stirring process is effectively discharged, preventing the generation and entrainment of bubbles, reducing the porosity in the slurry, and thus improving the density of the material; in addition, stirring under a vacuum environment enables the binder, conductive material and active material to fully contact and evenly disperse in the slurry, avoiding the problems of particle agglomeration and uneven distribution; the vacuum condition not only improves the fluidity and coating effect of the slurry, but also enhances the structural stability of the positive electrode sheet, effectively improving its electrochemical performance and durability in multiple charge and discharge cycles, so that the prepared positive electrode sheet has higher energy density and power characteristics, suitable for high-performance energy storage applications.
[0070] In some embodiments, the first stirring comprises the following process: stirring at a rotation speed of 80 rpm to 120 rpm for 4 min to 6 min, then stirring at a rotation speed of 250 rpm to 350 rpm for 4 min to 6 min, and finally stirring at a rotation speed of 500 rpm to 700 rpm for 250 min to 350 min;
[0071] The second stirring includes the following process: stirring at a rotation speed of 80 rpm to 120 rpm for 4 to 6 min, then stirring at a rotation speed of 250 rpm to 350 rpm for 4 to 6 min, and finally stirring at a rotation speed of 500 rpm to 700 rpm for 150 to 200 min;
[0072] The third stirring includes the following process: stirring at a rotation speed of 80 rpm to 120 rpm for 4 to 6 min, then stirring at a rotation speed of 250 rpm to 350 rpm for 4 to 6 min, and finally stirring at a rotation speed of 500 rpm to 700 rpm for 800 to 900 min;
[0073] High-speed stirring process: stirring at a speed of 1200 rpm to 1300 rpm for 150 min to 200 min;
[0074] Low-speed stirring process: Stir at a speed of 15rpm to 25rpm for 45min to 65min.
[0075] A detailed multi-stage stirring process is adopted, and the uniformity, stability and electrochemical performance of the active slurry are ensured through the combination of different speeds and durations. In the first stirring, stir at a lower speed (80rpm~120rpm) for 4~6min to allow the binder to gradually disperse in the organic solvent to prevent the violent mixing of the binder and the solvent from causing bubble formation and stratification. Then, further mix by stirring at a medium speed (250rpm~350rpm) to gradually merge the binder and the solvent to ensure the initial uniformity of the slurry. Finally, stir for a long time (250~350min) at a high speed (500rpm~700rpm) to ensure that the binder and the solvent are completely mixed to form a stable binder solution foundation, laying a good foundation for the subsequent addition of conductive substances.
[0076] In the second stirring, the conductive material is gradually added and the three-stage speed change is repeated to ensure that the conductive material is evenly distributed in the slurry. Short-term premixing at low and medium speeds can reduce the local conductivity differences caused by uneven dispersion of the conductive material. Subsequently, stirring is performed for a longer time (150 to 200 minutes) at a high speed (500 rpm to 700 rpm) to fully form the conductive network. In this way, the conductive material can be evenly distributed in the slurry, reducing the electrochemical performance loss caused by uneven resistance and ensuring the conductivity of the positive electrode sheet.
[0077] In the third stirring stage, the active material is added and fully dispersed and homogenized through similar three-stage stirring. First, stir at low speed (80rpm~120rpm) and medium speed (250rpm~350rpm) for 4~6min to provide a gentle stirring environment for the initial dispersion of the active material and avoid uneven dispersion caused by adding materials at high speed. Then stir at high speed (500rpm~700rpm) for 800~900min to ensure full fusion of the active material with the conductive material and binder, minimize agglomeration, and achieve the best dispersion and uniformity of the slurry.
[0078] Finally, all components in the slurry are thoroughly mixed by high-speed stirring (1200rpm~1300rpm, 150~200min) to ensure the conductivity and fluidity of the material. This is followed by low-speed stirring (15rpm~25rpm, 45~65min) to ensure that the tiny bubbles inside the slurry are released, reduce the porosity of the slurry, and make the slurry more stable. After this multi-stage, multi-rate stirring process, the prepared active slurry reaches an ideal state in terms of uniformity, conductivity, fluidity and stability, providing effective support for the high energy density and long cycle life of the positive electrode. This method achieves the perfect fusion of the components through fine stirring process control, thereby improving the electrochemical properties of the slurry and the service life of the electrode, so that it exhibits excellent energy storage effect and stability in practical applications.
[0079] This embodiment provides a positive electrode sheet, including a current collector and an active coating layer formed by curing the active slurry as described above on the surface, wherein the surface density of the active coating layer is 25 mg / cm 2 ~50mg / cm 2 , the thickness of the single-sided active coating layer is 100μm to 160μm;
[0080] The two sides of the current collector are coated with a graphene coating of 1 μm to 3 μm; the current collector comprises one of a smooth or frosted perforated aluminum foil or a non-porous aluminum foil.
[0081] The positive electrode sheet provided in this embodiment is formed by coating a specific active slurry on the surface of the current collector to have a surface density of 25 mg / cm 2 ~50mg / cm 2 The active coating layer with a thickness of 100μm to 160μm significantly improves the electrochemical performance and mechanical stability of the electrode; the thickness and surface density of the active coating layer ensure sufficient active material content, thereby enhancing the energy density and power density to meet the needs of efficient energy storage.
[0082] The current collector uses a perforated or non-porous aluminum foil with a 1μm to 3μm graphene coating on the surface, which further optimizes the conductivity; the graphene coating not only provides a good electron conduction path and reduces the internal resistance, but also improves the adhesion and structural strength between the current collector and the active layer, reducing the risk of coating shedding during cyclic charge and discharge; the perforated or non-porous aluminum foil design enables the electrode to adapt to different energy storage application requirements, among which the perforated aluminum foil increases the adhesion of the coating and the interface contact area, which helps to improve the stability of the structure and the cycle life of the electrode.
[0083] The present embodiment provides a method for preparing a positive electrode sheet, comprising the following steps: coating the active slurry on the surface of the current collector, with a coating roller speed of 300 mm / min to 350 mm / min and a roller speed ratio of 1.3 to 1.7, drying at a temperature of 120°C to 150°C, and then rolling to control the compaction degree to 2.0 to 2.4 g / cm 3 , and you get the positive electrode.
[0084] The positive electrode sheet preparation method of this embodiment ensures the uniformity, structural stability and excellent electrochemical performance of the electrode sheet by optimizing the coating, drying and rolling processes; first, the active slurry is evenly coated on the surface of the current collector at a coating roller speed of 300mm / min to 350mm / min, and a roller speed ratio of 1.3 to 1.7 is used to ensure that the thickness and surface density of the coating are consistent. Such process parameters control the spreading of the slurry on the surface of the current collector, making the active material distribution more uniform and avoiding performance fluctuations caused by uneven coating.
[0085] Later in The slurry is dried at a temperature of 100°C to ensure that the solvent in the slurry is completely volatilized, thereby forming a stable coating layer structure. This drying temperature effectively avoids cracking or shedding of the coating, while ensuring the density of the pole piece surface.
[0086] Finally, a roller pressing process is used to further compact the coating layer, so that the active material and the current collector are tightly combined, which significantly reduces the internal resistance of the electrode and enhances the conductivity and structural stability. The positive electrode prepared by this method not only has high energy density and power density, but also has good cycle stability and mechanical strength, and is suitable for high-performance energy storage applications.
[0087] The compaction degree of the positive electrode sheet is controlled at 2.0-2.4 g / cm 3 range, significantly improving the energy density and mechanical stability of the electrode; this compaction range ensures close contact between the active material particles, forms a continuous conductive network, reduces the internal porosity, thereby reducing the internal resistance of the electrode and improving the current conduction efficiency; at the same time, the appropriate compaction enhances the adhesion between the coating layer and the current collector, effectively reducing the risk of material peeling during the charge and discharge cycle, and extending the cycle life of the electrode.
[0088] In addition, controlling the compaction within this range can achieve a balance between high power density and mechanical toughness. Too low compaction may lead to insufficient energy density, while too high compaction may affect the conductivity and structural stability of the coating. By keeping the compaction within 2.0-2.4 g / cm 3 The positive electrode plates in these embodiments have higher energy storage efficiency, long-term cycle performance and good mechanical strength, and are suitable for energy storage devices requiring high energy density and high stability.
[0089] This embodiment provides an application of the above-mentioned positive electrode plate in electric vehicles, power grid energy storage, industrial automation and renewable energy systems.
[0090] The application of the positive electrode plate provided in this embodiment in electric vehicles, grid energy storage, industrial automation and renewable energy systems fully utilizes its advantages of high energy density, high power density and excellent cycle stability. In the field of electric vehicles, the positive electrode plate can support high-rate charging and discharging, meet the needs of electric vehicles for fast charging, long battery life and high power output, enable the battery to achieve rapid energy replenishment in a short time, extend the driving range and improve the driving experience. In addition, the high cycle life characteristics of the plate ensure that the electric vehicle battery maintains a stable capacity output during long-term use, thereby extending the overall life of the battery and reducing replacement frequency and maintenance costs.
[0091] In terms of grid energy storage, the battery made of the positive electrode sheet can efficiently store and release energy to adapt to the load balancing and peak-shaving needs of the power system. In areas where there is a significant difference in peak and valley power, the battery can store energy when power demand is low and release energy when power demand is high, providing continuous and stable power support for the grid. This energy storage capacity not only improves the stability and safety of grid operation, but also effectively utilizes the volatility of renewable energy generation and improves the grid-connected utilization rate of renewable energy.
[0092] In the field of industrial automation, high-performance batteries made from positive electrode sheets can provide reliable energy support for industrial equipment, especially in scenarios that require fast charging and discharging and high power output, such as robots and CNC machine tools in automated production lines. Its high power density enables the equipment to continue to operate efficiently even under high load conditions, avoiding production interruptions caused by insufficient power and improving the automation level and production efficiency of the production line.
[0093] In addition, in renewable energy systems, the application of this positive electrode can help balance the volatility of renewable energy such as solar energy and wind energy. Since the power generation of renewable energy is unstable, the addition of an efficient energy storage system can store energy when the sun or wind is strong, and release it when demand increases or the power supply is insufficient, thereby ensuring the stability of energy supply. Its long cycle life and high efficiency enable energy storage equipment to operate stably for a long time, providing a reliable energy buffer for renewable energy systems, and promoting the efficient use of renewable energy and the promotion of clean energy.
[0094] In summary, the positive electrode plate in this embodiment has shown broad application prospects in electric vehicles, grid energy storage, industrial automation and renewable energy systems due to its excellent electrochemical properties. It has promoted technological progress and sustainable development in many fields by improving energy utilization efficiency, reducing costs and extending equipment life.
[0095] Example
[0096] Example 1
[0097] Example 1 provides an active slurry, the active slurry includes an active material and an organic solvent, and the solid content is 45wt%; wherein the organic solvent is N-methylpyrrolidone;
[0098] The raw materials of active materials are calculated by mass fraction, including:
[0099] Active material, 93.5wt%; Binder, 4.0wt%; Conductive material, 2.5wt%;
[0100] The active material includes lithium nickel cobalt manganese oxide and activated carbon, and the mass ratio of lithium nickel cobalt manganese oxide to the activated carbon is 1:10; the binder is polyvinylidene fluoride; the conductive material includes graphene and carbon black, and the mass ratio of graphene to carbon black is 1.0:1.0.
[0101] Embodiment 1 provides a method for preparing an active slurry, comprising the following steps:
[0102] At a vacuum degree of 10 -2 Pa, the binder was added to the organic solvent, stirred at 100 rpm for 5 min, then the speed was increased to 300 rpm for 5 min, and finally stirred at 600 rpm for 300 min to obtain a uniform binder solution.
[0103] A conductive material was added to the adhesive solution, and the mixture was stirred at 100 rpm for 5 min, then at 300 rpm for 5 min, and finally at 600 rpm for 180 min to ensure uniform dispersion of the conductive agent, thereby obtaining a conductive adhesive solution.
[0104] Active material was added to the conductive adhesive solution, and after mixing, the mixture was stirred at 100 rpm for 5 min, then increased to 300 rpm for 5 min, and finally stirred at 600 rpm for 840 min; thereafter, the stirring speed was increased to 1200 rpm, stirred at high speed for 180 min, and finally stirred at low speed at 20 rpm for 50 min to complete the mixing of the slurry and obtain the active slurry.
[0105] Embodiment 1 also provides a positive electrode sheet, including a current collector and an active coating layer formed by curing the active slurry on its surface; the active coating layer has a surface density of 35 mg / cm 2 , the thickness of the single-sided active coating layer is 130μm;
[0106] The current collector is a smooth perforated aluminum foil with a thickness of 12 μm and coated with a 1 μm graphene coating on both sides.
[0107] Embodiment 1 also provides a method for preparing a positive electrode sheet, comprising the following steps:
[0108] The active slurry was evenly coated on both sides of the aluminum foil current collector, and the speed of the coating roller was adjusted to 330 mm / min, and the roller speed ratio was set to 1.5. Subsequently, the drying was carried out at a drying temperature of 140 °C to ensure rapid evaporation of the solvent. Then, the coating density of the double-sided positive electrode sheet was controlled at 35 mg / cm by adjusting the parameters of the coating machine. 2 The thickness of the single-sided active coating is 130 μm. Finally, the roller pressing process is carried out, and the compaction degree is controlled at 2.2 g / cm by using the method of multiple roller pressing. 3 To ensure that the electrode has good uniformity and density consistency, a positive electrode is obtained.
[0109] Example 2
[0110] Example 2 provides an active slurry, the active slurry includes an active material and an organic solvent, and the solid content is 50wt%; wherein the organic solvent is dimethylformamide;
[0111] The raw materials of active materials are calculated by mass fraction, including:
[0112] Active material, 95wt%; Binder, 3.0wt%; Conductive material, 2.0wt%;
[0113] The active material includes lithium nickel cobalt manganese oxide and activated carbon, and the mass ratio of lithium nickel cobalt manganese oxide to activated carbon is 5:5; the binder is polytetrafluoroethylene; the conductive material includes graphene and carbon black, and the mass ratio of graphene to carbon black is 0.2:1.0.
[0114] Embodiment 2 provides a method for preparing an active slurry, comprising the following steps:
[0115] At a vacuum degree of 10 -2 Pa, the binder was added to the organic solvent, stirred at 80 rpm for 6 min, then the speed was increased to 250 rpm for 6 min, and finally stirred at 500 rpm for 350 min to obtain a uniform binder solution.
[0116] A conductive material was added to the adhesive solution, and stirring was continued at 80 rpm for 6 min, then at 250 rpm for 6 min, and finally at 500 rpm for 200 min to ensure uniform dispersion of the conductive agent, thereby obtaining a conductive adhesive solution.
[0117] Active material was added to the conductive adhesive solution, and after mixing, it was stirred at 80 rpm for 6 minutes, then increased to 250 rpm for 6 minutes, and finally stirred at 500 rpm for 900 minutes; thereafter, the stirring speed was increased to 1200 rpm, stirred at high speed for 200 minutes, and finally stirred at low speed of 15 rpm for 55 minutes to complete the mixing of the slurry and obtain active slurry.
[0118] Embodiment 2 also provides a positive electrode sheet, including a current collector and an active coating layer formed by curing the active slurry on its surface; the active coating layer has a surface density of 25 mg / cm 2 , the thickness of the single-sided active coating layer is 100μm;
[0119] The current collector is a smooth perforated aluminum foil with a thickness of 12 μm and coated with a 3 μm graphene coating on both sides.
[0120] Embodiment 2 also provides a method for preparing a positive electrode sheet, comprising the following steps:
[0121] The active slurry was evenly coated on both sides of the aluminum foil current collector, and the speed of the coating roller was adjusted to 320 mm / min, and the roller speed ratio was set to 1.7; then, it was dried at a drying temperature of 150 ° C to ensure rapid evaporation of the solvent; then, the coating density of the double-sided positive electrode sheet was controlled at 25 mg / cm by adjusting the parameters of the coating machine. 2 The thickness of the single-sided active coating is 100 μm. Finally, the roller pressing process is carried out, and the compaction degree is controlled at 2.2 g / cm by using the method of multiple roller pressing. 3 To ensure that the electrode has good uniformity and density consistency, a positive electrode is obtained.
[0122] Example 3
[0123] Example 3 provides an active slurry, the active slurry includes an active material and an organic solvent, and the solid content is 55wt%; wherein the organic solvent is N-methylpyrrolidone;
[0124] The raw materials of active materials are calculated by mass fraction, including:
[0125] Active material, 97.5wt%; Binder, 1.5wt%; Conductive material, 1.0wt%;
[0126] The active material includes lithium nickel cobalt manganese oxide and activated carbon, and the mass ratio of lithium nickel cobalt manganese oxide to activated carbon is 10:1; the binder is polyvinyl alcohol; the conductive material includes carbon tubes and carbon black, and the mass ratio of carbon tubes to carbon black is 0.2:1.0.
[0127] Embodiment 3 provides a method for preparing an active slurry, comprising the following steps:
[0128] At a vacuum degree of 10 -2 Pa, the binder was added to the organic solvent, stirred at 120 rpm for 4 min, then the speed was increased to 350 rpm for 4 min, and finally stirred at 700 rpm for 250 min to obtain a uniform binder solution.
[0129] A conductive material was added to the adhesive solution, and stirring was continued at 120 rpm for 4 min, then at 350 rpm for 4 min, and finally at 700 rpm for 150 min to ensure uniform dispersion of the conductive agent, thereby obtaining a conductive adhesive solution.
[0130] Active material was added to the conductive adhesive solution, and after mixing, it was stirred at 120 rpm for 4 min, then increased to 350 rpm for 4 min, and finally stirred at 700 rpm for 800 min; thereafter, the stirring speed was increased to 1300 rpm, stirred at high speed for 150 min, and finally stirred at low speed at 25 rpm for 45 min to complete the mixing of the slurry and obtain active slurry.
[0131] Embodiment 3 also provides a positive electrode sheet, including a current collector and an active coating layer formed by curing the active slurry on its surface; the active coating layer has a surface density of 50 mg / cm 2 , the thickness of the single-sided active coating layer is 160μm;
[0132] The current collector is a smooth perforated aluminum foil with a thickness of 15 μm and coated with a 2 μm graphene coating on both sides.
[0133] Embodiment 3 also provides a method for preparing a positive electrode sheet, comprising the following steps:
[0134] The active slurry was evenly coated on both sides of the aluminum foil current collector, and the speed of the coating roller was adjusted to 350 mm / min, and the roller speed ratio was set to 1.3; then, it was dried at a drying temperature of 120 °C to ensure rapid evaporation of the solvent; then, the coating density of the double-sided positive electrode sheet was controlled at 50 mg / cm by adjusting the parameters of the coating machine. 2 The thickness of the single-sided active coating is 160 μm. Finally, the roller pressing process is carried out, and the compaction degree is controlled at 2.4 g / cm by using the method of multiple roller pressing. 3 To ensure that the electrode has good uniformity and density consistency, a positive electrode is obtained.
[0135] Example 4
[0136] The difference between an active slurry provided in Example 4 and Example 3 is that the conductive material in Example 4 includes carbon tubes and carbon black, and the mass ratio of the carbon tubes to the carbon black is 1:1.
[0137] The preparation method of the active slurry, the positive electrode sheet, and the preparation method of the positive electrode sheet provided in Example 4 are the same as those in Example 3.
[0138] Comparative Example
[0139] Comparative Example 1
[0140] Comparative Example 1 provides an active slurry which is different from Example 1 in that the solid content of the active slurry is 40 wt %.
[0141] The active slurry preparation method, positive electrode sheet, and positive electrode sheet preparation method provided in Comparative Example 1 are the same as those in Example 1.
[0142] Comparative Example 2
[0143] Comparative Example 2 provides an active slurry which is different from Example 1 in that the solid content of the active slurry is 65 wt %.
[0144] The active slurry preparation method, positive electrode sheet, and positive electrode sheet preparation method provided in Comparative Example 2 are the same as those in Example 1.
[0145] Comparative Example 3
[0146] The active slurry provided in Comparative Example 3 is the same as that in Example 1.
[0147] The difference between the preparation method of an active slurry provided in Comparative Example 3 and Example 1 is that the preparation method of the active slurry provided in Comparative Example 1 does not perform gradient stirring, and is specifically as follows:
[0148] Comparative Example 3 provides a method for preparing an active slurry, comprising the following steps:
[0149] At a vacuum degree of 10 -2 Pa, the binder was added to the organic solvent and stirred at 600 rpm for 300 min to obtain a uniform binder solution;
[0150] Adding a conductive material to the adhesive solution, stirring at 600 rpm for 180 min, to obtain a conductive adhesive solution;
[0151] The active material was added to the conductive adhesive solution, and stirred at 600 rpm for 840 min. Then, the stirring speed was increased to 1200 rpm, stirred at high speed for 180 min, and finally stirred at low speed at 20 rpm for 50 min to complete the mixing of the slurry and obtain the active slurry.
[0152] The positive electrode sheet and the preparation method of the positive electrode sheet provided in Comparative Example 3 are the same as those in Example 1.
[0153] Comparative Example 4
[0154] The active slurry provided in Comparative Example 4 is the same as that in Example 1.
[0155] The difference between the method for preparing an active slurry provided in Comparative Example 4 and Example 1 is that the method for preparing the active slurry provided in Comparative Example 2 does not involve stirring under a vacuum environment.
[0156] The positive electrode sheet and the preparation method of the positive electrode sheet provided in Comparative Example 4 are the same as those in Example 1.
[0157] Comparative Example 5
[0158] The active slurry provided in Comparative Example 5 is the same as that in Example 1.
[0159] Comparative Example 5 provides a method for preparing an active slurry, which differs from Example 1 in that high-speed stirring and low-speed stirring are not performed, and is specifically as follows:
[0160] Comparative Example 5 provides a method for preparing an active slurry, comprising the following steps:
[0161] At a vacuum degree of 10 -2 Pa, the binder was added to the organic solvent, stirred at 100 rpm for 5 min, then the speed was increased to 300 rpm for 5 min, and finally stirred at 600 rpm for 300 min to obtain a uniform binder solution.
[0162] A conductive material was added to the adhesive solution, and the mixture was stirred at 100 rpm for 5 min, then at 300 rpm for 5 min, and finally at 600 rpm for 180 min to ensure uniform dispersion of the conductive agent, thereby obtaining a conductive adhesive solution.
[0163] The active material was added to the conductive adhesive solution, and after mixing, the mixture was stirred at 100 rpm for 5 minutes, then increased to 300 rpm for 5 minutes, and finally stirred at 600 rpm for 840 minutes; the slurry was mixed to obtain an active slurry.
[0164] The positive electrode sheet and the preparation method of the positive electrode sheet provided in Comparative Example 5 are the same as those in Example 1.
[0165] Comparative Example 6
[0166] Comparative Example 6 provides an active slurry, and the preparation method of the active slurry is the same as that of Example 1.
[0167] Comparative Example 6 provides a positive electrode sheet which is different from Example 1 in that the active coating surface density is 20 mg / cm 2 .
[0168] Comparative Example 6 provides a method for preparing a positive electrode sheet. The difference from Example 1 is that by adjusting the parameters of the coating machine, the double-sided coating density of the positive electrode sheet is controlled to be 20 mg / cm 2 .
[0169] Comparative Example 7
[0170] Comparative Example 7 provides an active slurry, and the preparation method of the active slurry is the same as that of Example 1.
[0171] Comparative Example 7 provides a positive electrode sheet which is different from Example 1 in that the surface density of the active coating is 55 mg / cm 2 .
[0172] Comparative Example 7 provides a method for preparing a positive electrode sheet. The difference from Example 1 is that by adjusting the parameters of the coating machine, the double-sided coating density of the positive electrode sheet is controlled to be 55 mg / cm 2 .
[0173] Comparative Example 8
[0174] Comparative Example 8 provides an active slurry, and the preparation method of the active slurry is the same as that of Example 1.
[0175] Comparative Example 8 provides a positive electrode plate which is different from Example 1 in that the thickness of the single-sided active coating layer is 90 μm.
[0176] Comparative Example 8 provides a positive electrode sheet which is different from Example 1 in that, by adjusting the parameters of the coating machine, the thickness of the single-sided active coating is 90 μm.
[0177] Comparative Example 9
[0178] Comparative Example 9 provides an active slurry, and the preparation method of the active slurry is the same as that of Example 1.
[0179] Comparative Example 9 provides a positive electrode sheet which is different from Example 1 in that the surface of the current collecting plate is not coated with graphene.
[0180] Comparative Example 9 provides a method for preparing a positive electrode sheet that is the same as that of Example 1.
[0181] Application Examples
[0182] The positive electrode sheets provided in Examples 1-4 and Comparative Examples 1-9 were respectively assembled into 2032 button cells in a glove box in an argon environment, with the concentrations of humidity (water) and oxygen being less than 1 ppm. The positive electrode sheets provided in Example 1 were cut into disc electrodes with a diameter of 12 mm, a PP diaphragm (Celgard 2500) was used, pure lithium foil was used as the counter electrode, and LiPF6 (1.0 M, ethylene carbonate, dimethyl carbonate, volume ratio of 1:1) was used as the electrolyte.
[0183] Performance Testing
[0184] Adhesion test of active coating layer on electrode surface
[0185] The positive electrode sheets provided in Examples 1-4 and Comparative Examples 1-9 were tested by a “cross-hatch test” to evaluate the adhesion between the active coating layer and the current collector.
[0186] 1. Purpose of the experiment
[0187] The cross-hatch test is used to determine the adhesion strength between the active coating layer and the current collector on the positive electrode. By scratching a specific grid pattern on the coating and combining it with tape peeling, the adhesion level of the coating can be intuitively evaluated.
[0188] 2. Test equipment
[0189] Scratching knife: Multi-blade scribing knife is commonly used, the spacing is usually 1mm or 2mm, choose the appropriate spacing according to the thickness of the coating layer. The cutting edge of the scribing knife is sharp and the spacing is uniform to ensure the scribing effect.
[0190] Transparent tape: Generally, choose a transparent tape with moderate adhesion (such as 3M's 600 series tape) to ensure that the coating will not be excessively damaged during the peeling process.
[0191] Magnifying glass or microscope: used to observe the coating condition after scribe, the magnification can be between 10x and 20x.
[0192] Rulers and rulers: Used to measure the depth and spacing of scratches.
[0193] 3. Experimental steps
[0194] Sample preparation: Make sure the positive electrode sample is dry and clean, and fix it on a flat surface to prevent it from moving during the test.
[0195] Grid operation: Use a grid knife to scratch perpendicular parallel lines on the coating surface to form a grid pattern. The recommended size is a square grid with a spacing of 1mm or 2mm (such as 6x6 or 10x10). When scratching, make sure that the blade cuts through the coating to the substrate surface without damaging the current collector.
[0196] Taping: Apply transparent tape to the marked grid area and press the tape to ensure full contact with the coating surface.
[0197] Peeling operation: Peel off the tape quickly at an angle of about 45° and observe the peeling of the coating within the grid.
[0198] Result observation: Observe the cross-cut area through a magnifying glass or microscope to evaluate the peeling of the coating.
[0199] 4. Result evaluation
[0200] Adhesion is graded according to the degree of peeling of the coating. Generally, the adhesion grade of the cross-cut test is divided into 0 to 5 levels, and the specific standards are as follows:
[0201] Level 0: No peeling or very little peeling, the coating is intact, indicating excellent adhesion.
[0202] Level 1: There is a small amount of peeling at the cut of the grid, but the peeling area is less than 5%, and the adhesion of the coating layer is very good.
[0203] Level 2: The peeling area is between 5% and 15%, and the adhesion is good.
[0204] Level 3: The peeling area is between 15% and 35%, indicating that the adhesion is average.
[0205] Level 4: The peeling area is between 35% and 65%, indicating poor adhesion.
[0206] Level 5: Most of the coating peels off, and the peeling area exceeds 65%, indicating that the adhesion is very poor.
[0207] Generally, adhesion levels 0 to 2 are considered to meet the requirements, while levels 3 and below may require process improvements or formulation adjustments.
[0208] 5. Test conditions and precautions
[0209] Selection of grid spacing: Select the appropriate spacing and blade depth according to the coating thickness to avoid damage to the current collector.
[0210] Tape selection: Tapes with too high or too low adhesion will affect the test results. Usually, transparent tapes with medium adhesion are selected.
[0211] Peeling speed: Maintain a 45° angle and peel quickly to ensure test stability and repeatability.
[0212] Environmental Conditions: Test at room temperature and in dry conditions to avoid high temperature or humidity that may affect adhesion.
[0213] The positive electrode sheets provided in Examples 1-4 and Comparative Examples 1-9 were tested according to the above-mentioned “scratch test”, and the test results are shown in Table 1 below.
[0214] Table 1 Adhesion grade of active coating layer on positive electrode surface of Examples 1-4 and Comparative Examples 1-9
[0215]
[0216] LAND Battery Test
[0217] Specific capacity test: including the specific capacity results of the examples and comparative samples, used to show the capacity differences of different positive electrode sheets under the same conditions.
[0218] Rate performance test: The charge and discharge capacity changes at different rates (such as 0.5C, 1C, 2C, 5C and 10C) were analyzed. It is expected that the positive electrode sheet of the embodiment maintains a higher capacity at a high rate, while the comparative example may show a greater capacity drop.
[0219] Cycle stability test: The positive electrode was cycled for 2,000 times, and the changes in specific capacity and charge and discharge efficiency were recorded to evaluate its cycle life. The examples showed excellent stability, while the capacity retention of some comparative examples was relatively low.
[0220] Electrochemical impedance spectroscopy (EIS): used to measure the interface impedance and charge transfer impedance, and further verify the conductive performance of the positive electrode. The impedance of the embodiments is generally low, which is suitable for high-power applications.
[0221] The capacity test, rate performance test and cycle stability test of the 2032 button cell composed of the positive electrode sheet provided in Example 1 are as follows: Figure 1-3 The specific analysis is as follows:
[0222] 1. Specific capacity test
[0223] Depend on Figure 1 It can be seen that Figure 1 The charge and discharge curves of the positive electrode material in different voltage ranges are shown, with the abscissa being the specific capacity (mAh / g) and the ordinate being the voltage (V). As can be seen from the figure, there are certain differences in the voltage curves during the charging and discharging processes, indicating that the material has voltage polarization during the charging and discharging process. This polarization may be due to factors such as internal resistance and interfacial impedance during the electrochemical reaction, which affects the electrochemical properties of the material. The charging curve remains relatively stable on the high voltage platform, indicating that the lithium ion embedding of the electrode material is relatively uniform within this voltage range, and there is no significant phase change or material structure damage. This stable voltage platform is particularly important in battery applications because it can provide stable energy output, thereby achieving higher energy density.
[0224] During the discharge process, the voltage platform is relatively stable and presents a relatively symmetrical shape with the charging process, indicating that the discharge process of the material has good reversibility and stability. This symmetry shows that the material maintains good structural integrity during the charge and discharge cycle, especially no serious structural expansion or pulverization occurs during the charge and discharge conversion process. The stability of the discharge platform is directly related to the energy output efficiency of the battery. The relatively stable discharge curve shows that the material can provide continuous and stable energy output, which helps to improve the stability and consistency of the entire battery system.
[0225] In addition, the difference between the charge curve and the discharge curve, namely the "voltage hysteresis" phenomenon, can be used to measure the electrochemical impedance of the electrode material. Small voltage hysteresis indicates that the material has low internal resistance and electrochemical impedance, which is beneficial to improving rate performance and energy efficiency. Lower voltage polarization also helps to reduce energy loss during charging and discharging, thereby improving the overall efficiency of the battery. Overall, the material has a smooth and symmetrical charge and discharge curve, good electrochemical reversibility and small internal resistance, and can provide stable capacity output over a wide voltage range, verifying its suitability as a high-performance positive electrode material.
[0226] 2. Rate performance test
[0227] Depend on Figure 2 It can be seen that Figure 2 The battery's charge and discharge specific capacity at different rates is shown, including the test results of 0.5C, 1C, 2C, 5C and 10C rates. It can be seen that as the rate increases, the specific capacity decreases. This is because at high rates, the ion diffusion rate and electron conduction rate of the electrode material are limited, resulting in some active materials failing to fully participate in the reaction. Therefore, the decrease in capacity at high rates is normal, but it is observed that the material still maintains a high specific capacity at 10C, which reflects the excellent rate performance of the positive electrode material.
[0228] The results of the rate performance test show that at 0.5C and 1C, the specific capacity of the battery is close to the theoretical capacity, indicating that the material can fully release its energy storage capacity at low rates. As the rate increases to 2C and 5C, the capacity decreases slightly, but still remains at a high level, which shows that the material still has good fast charging and discharging performance at higher rates and can provide stable energy output in a short time. At the highest rate of 10C, although the specific capacity decreases, it still shows a relatively high energy storage capacity, which is ideal for high power requirements in practical applications.
[0229] In addition, the figure shows that the charge and discharge specific capacities are basically the same, indicating that the coulombic efficiency of the battery is high at each rate. The stability of the coulombic efficiency indicates that the battery has a high energy conversion efficiency during the charge and discharge process at different rates, the reversibility of the electrochemical reaction is good, and there is no significant side reaction or irreversible loss of the material. This high-efficiency electrochemical reaction also shows that the material has strong structural stability and low resistance, enabling it to maintain high battery performance under different power output conditions. In summary, the rate performance test shows that the material can maintain high capacity and efficiency over a wide range from low to high rates, and is suitable for use in energy storage systems with high power requirements.
[0230] 3. Cycle stability
[0231] Depend on Figure 3 It can be seen that Figure 3 The changes in the battery's capacity retention rate and charge and discharge efficiency during a long cycle are shown. It can be observed that after 2000 charge and discharge cycles, the battery's charge specific capacity and discharge specific capacity have basically not decayed significantly, and the charge and discharge efficiency remains at a high level. This excellent cycle stability shows that the positive electrode material has excellent structural stability during long-term and high-frequency charge and discharge processes. The ability to maintain a high capacity retention rate during a long cycle indicates that the material's electrochemical reaction is highly reversible and can still provide sufficient active sites after multiple cycles.
[0232] During the cycle, the battery's discharge specific capacity remained at a relatively stable level, indicating that the material did not undergo significant structural changes or activity loss during the charge and discharge process. This property of the material is crucial to extending battery life, because in practical applications, batteries often need to undergo thousands of charge and discharge cycles. The ability to maintain high capacity for such a long time indicates that the material has good structural durability during the lithium insertion and delithiation process, and no serious crystal structure collapse, particle pulverization or electrolyte decomposition has occurred, which is of great significance for the development of high-performance batteries.
[0233] In addition, the charge and discharge efficiency is always close to 100%, indicating that the material has an extremely high coulombic efficiency during the cycle. High coulombic efficiency means that the battery has almost no irreversible capacity loss during each cycle, indicating that the material has excellent chemical and mechanical stability and fewer side reactions. Through this cycle stability test, it can be seen that the positive electrode material not only has the ability to maintain high capacity for a long time, but also its structure is maintained over multiple cycles, making it suitable for energy storage systems that require long life and high stability, such as electric vehicles and large-scale energy storage power stations. Overall, the cycle stability test results verify the high durability and high efficiency of the positive electrode material, providing strong support for its reliability in practical applications.
[0234] The 2032-type button cells obtained by assembling the positive electrode sheets provided in Examples 2-4 and Comparative Examples 1-9 under the same conditions were subjected to capacity tests, rate performance tests and cycle stability tests using the above-mentioned test methods under the same conditions. The test results are shown in Table 2.
[0235] Table 2 Test results of positive electrode sheets of Examples 1-4 and Comparative Examples 1-9 assembled into 2032 button batteries
[0236]
[0237] As shown in Table 2, there are significant differences between Examples 1-4 and Comparative Examples 1-9 in terms of electrochemical performance indicators such as initial specific capacity, rate performance, cycle stability, and charge transfer impedance. These differences can be attributed to the optimization degree of different positive electrode material formulas and preparation processes.
[0238] Initial specific capacity
[0239] The initial specific capacity of Example 1 reaches 220 mAh / g, which is slightly higher than that of other Examples 2-4, indicating that good results have been achieved in optimizing the ratio of active materials and conductive agents. In contrast, the initial specific capacity of the comparative examples is generally low, with the highest comparative example 1 being only 200 mAh / g, indicating that the capacity of the positive electrode material of the comparative example is poor in the initial state and cannot provide a high storage capacity.
[0240] Rate performance
[0241] Examples 1-4 show good capacity retention at different rates (0.5C to 10C). For example, at a rate of 10C, the specific capacity of Example 1 still reaches 180mAh / g, which is significantly higher than the sample of the comparative example. The capacity of the comparative example decreases more significantly with increasing rate, especially at high rates (such as 5C and 10C), the specific capacity decreases significantly. The excellent rate performance of the embodiment shows its good conductivity and ion diffusion capacity, so that it can still maintain a high specific capacity at high rates.
[0242] Cyclic stability
[0243] The capacity retention rate of Example 1 after 2000 cycles reached 95%, showing an excellent cycle life, while the other Examples (2-4) also maintained a capacity retention rate of about 92-94%, respectively. In contrast, the capacity retention rates of the comparative samples are generally lower, with the highest comparative example 1 only maintaining 80% of the capacity, and other comparative samples even dropping to about 65%. This shows that the materials in the examples have strong structural stability during the cycle process and can better resist structural changes and electrochemical damage caused by repeated charge and discharge.
[0244] Charge transfer resistance
[0245] The charge transfer impedance of the embodiments is generally low, such as the internal resistance of Example 1 is 2.5mΩ, while the charge transfer impedance of the comparative examples is higher, usually above 4.5mΩ, and the highest comparative example 9 reaches 15.2mΩ. Low internal resistance means lower electrochemical polarization and higher electronic conduction efficiency, so the lower impedance of the embodiments indicates that its conductive network is more complete and suitable for high-rate discharge applications. The comparative examples have high impedance, which may lead to poor rate performance and fail to meet the needs of high-power applications.
[0246] In summary, the positive electrode plates of Examples 1-4 are superior to the comparative samples in terms of initial specific capacity, rate performance, cycle stability and charge transfer impedance. This shows that the positive electrode materials in the examples have achieved higher electrochemical performance indicators through the optimization of formulation and process, and can adapt to energy storage applications with high energy density and high power density; the examples perform particularly well in high rates and long cycles, showing strong rapid charge and discharge capabilities and long life characteristics. This is crucial for applications in fields such as electric vehicles, grid energy storage, and industrial automation, and can maintain stable performance in high-power and high-frequency usage environments; the low impedance of the examples further demonstrates its excellent electrical conductivity and ion conduction capabilities, which are suitable for high-rate discharge requirements. The high impedance of the comparative samples limits their rate performance and results in greater energy losses.
[0247] Overall, the positive electrode sheets of Examples 1-4 exhibit excellent electrochemical performance and are suitable for high-end energy storage devices that require high energy density, excellent rate performance, and long cycle life, while the comparative samples have poor applicability due to performance limitations. These data provide experimental support for the material advantages of the present invention and also lay the foundation for its promotion in practical applications.
[0248] For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived from them are still within the scope of protection of the claims of the invention.
Claims
1. An active slurry, characterized in that: The active slurry comprises an active material and an organic solvent, and the solid content of the active slurry is 45wt% to 60wt%; The raw materials of the active material include, by mass fraction: Active matter, 93.5 wt% to 97.5 wt%; Binder, 1.5wt% to 4.0wt%; Conductive material, 1.0wt% to 2.5wt%.
2. An active slurry according to claim 1, characterized in that: The active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and activated carbon; The binder includes one or more of polyvinylidene fluoride, polyvinyl alcohol and polytetrafluoroethylene; The conductive material includes one or more of carbon black, graphene, carbon tubes, and conductive graphite; The organic solvent is one or more of N-methylpyrrolidone, dimethylformamide and dimethyl sulfoxide.
3. An active slurry according to claim 2, characterized in that: The active material includes lithium nickel cobalt manganese oxide and activated carbon, and the mass ratio of the lithium nickel cobalt manganese oxide to the activated carbon is 1:10 to 10:
1.
4. The active slurry according to claim 2, characterized in that: The conductive material includes graphene and carbon black, and the mass ratio of the graphene to the carbon black is 0.2:1.0 to 1.0:1.0; Alternatively, the conductive material includes carbon tubes and carbon black, and the mass ratio of the carbon tubes to the carbon black is 0.2:1.0 to 1.0:1.
0.
5. A method for preparing the active slurry according to any one of claims 1 to 4, characterized in that: The process includes: Under vacuum, the binder is added to the organic solvent for the first stirring, the conductive material is then added for the second stirring, and the active material is finally added for the third stirring. After preliminary mixing, high-speed stirring and low-speed stirring are performed in sequence to obtain the active slurry.
6. The method for preparing an active slurry according to claim 5, characterized in that: Under the vacuum state, the vacuum degree is 10 -2 Pa~10 -3 Pa.
7. The method for preparing an active slurry according to claim 5, characterized in that: The first stirring comprises the following process: stirring at a rotation speed of 80 rpm to 120 rpm for 4 min to 6 min, then stirring at a rotation speed of 250 rpm to 350 rpm for 4 min to 6 min, and finally stirring at a rotation speed of 500 rpm to 700 rpm for 250 min to 350 min; The second stirring comprises the following process: stirring at a rotation speed of 80 rpm to 120 rpm for 4 min to 6 min, then stirring at a rotation speed of 250 rpm to 350 rpm for 4 min to 6 min, and finally stirring at a rotation speed of 500 rpm to 700 rpm for 150 min to 200 min; The third stirring includes the following process: stirring at a rotation speed of 80 rpm to 120 rpm for 4 min to 6 min, then stirring at a rotation speed of 250 rpm to 350 rpm for 4 min to 6 min, and finally stirring at a rotation speed of 500 rpm to 700 rpm for 800 min to 900 min; The high-speed stirring process: stirring at a rotation speed of 1200 rpm to 1300 rpm for 150 min to 200 min; The low-speed stirring process is as follows: stirring at a rotation speed of 15 rpm to 25 rpm for 45 min to 65 min.
8. A positive electrode sheet, characterized in that: The invention comprises a current collector and an active coating layer formed by curing the active slurry as claimed in any one of claims 1 to 4 on the surface, wherein the surface density of the active coating layer is 25 mg / cm 2 ~50mg / cm 2 , the thickness of the active coating layer on one side is 100 μm to 160 μm; Both sides of the current collector are coated with a graphene coating of 1 μm to 3 μm; the current collector comprises one of a smooth or frosted perforated aluminum foil or a non-porous aluminum foil.
9. A method for preparing a positive electrode sheet as claimed in claim 8, characterized in that: The process comprises the following steps: coating the active slurry on the surface of the current collector, with the coating roller speed being 300 mm / min to 350 mm / min and the roller speed ratio being 1.3 to 1.7, drying at a temperature of 120°C to 150°C, and then rolling to control the compaction degree to be 2.0 to 2.4 g / cm 3 , and the positive electrode sheet is obtained.
10. An application of the positive electrode plate as claimed in claim 8 in electric vehicles, grid energy storage, industrial automation and renewable energy systems.
Citation Information
Patent Citations
Electrode plate of graphene coating modified lithium secondary battery and manufacturing method thereof
CN102208598A
High-temperature hybrid supercapacitor and fabrication method thereof
CN105551822A
Lithium ion battery positive electrode paste, preparation method thereof, lithium ion battery and preparation method of lithium ion battery
CN108134066A
Positive electrode slurry and preparation method thereof, positive plate and preparation method thereof, lithium ion battery and application thereof
CN111029581A
Preparation method of positive pole piece of lithium ion battery
CN114156441A